Taking measure of personalized medicine: the proteome. (March 2013) - Steele, Fintan; Gold, Larry
Good medicine begins, by and large, with measurements. For medicine to become truly personalized, it is critical that the right measurements are made and interpreted. Although genomics holds great promise for deepening our understanding of biology, we believe that a perhaps more critical and transformative measurement for medicine is proteomics, which has lagged behind genomics for largely technological reasons. Proteins uniquely provide a real-time, clinically relevant measure of individual patients. We describe here an entirely new proteomics technology that makes the measure of proteins from biological samples as straightforward as measuring genes, and list some of the applications that have already been performed.